Nurse-performed venous sheath removal in patients undergoing radiofrequency catheter ablation for atrial fibrillation: a randomised study. (April 2019) - Rolantova, Lucie; Bulava, Alan; Eisenberger, Martin; Chloubova, Ivana; Tothova, Valerie; Hanis, Jiri
Background: Catheter ablation procedures have recently become a widely accepted method for treating cardiac arrhythmias, and referrals for these procedures have been steadily increasing. As a result, it is now common that sheath removal is handled as a nursing procedure. Regardless of who performs the sheath removal, it is important to extract ablation sheaths without any early or late complications. Objective: The aim of this randomised study was to determine the safety of sheath extraction after heparin reversal with low-dose protamine sulfate in patients undergoing radiofrequency catheter ablation for atrial fibrillation and whether these sheaths can be safely removed by nurses. Methods: Eighty-one patients were randomly assigned to either receiving protamine to reverse heparin after an ablation ( n =40) or to the standard protocol without heparin reversal ( n =41). Nurse-led sheath removal was done in the cath lab (protamine group) or on the ward (standard group) as soon as activated partial thromboplastin time dropped below 60 s. All adverse events, groin compression time, immobilisation time and procedure characteristics were recorded. Results: The manual compression time for the standard group was significantly longer than for the protamine group (15.9 ± 2.5 vs. 21.9 ± 3.1 minutes, P <0.001) as well as the total immobilisation time (13.2 ± 2.4 vs. 20.3 ± 3.8 hours, P =0.01). Minor groin haematomas occurred less frequently in the protamine group (4 vs. 12, P =0.02) and the haematomas tended to be smaller (4.1 ± 2.1 vs. 5.2 ± 2.5 cm, P =0.09). No serious adverse events were observed when the femoral sheaths were extracted by specially trained staff nurses. Conclusion: Fewer and milder complications and shorter immobilisation times were reported with protamine reversal compared to the conventional method. Staff nurses can safely remove femoral venous sheaths after a radiofrequency ablation for atrial fibrillation.